Chemical descriptors of yttria-stabilized zirconia at low defect concentration: an ab initio study. - Parkes,MA; Refson,K; d'Avezac,M; Offer,GJ; Brandon,NP; Harrison,NM (Journal of Physical Chemistry A, 2015)
Yttria-stabilized zirconia (YSZ) is an important oxide ion conductor with applications in solid oxide fuel cells (SOFCs) and oxygen sensing devices. Doping the cubic phase of zirconia (c-ZrO2) with yttria (Y2O3) is isoelectronic, as two Zr(4+) ions are replaced by two Y(3+) ions, plus a charge compensating oxygen vacancy (Ovac). Typical doping concentrations include 3, 8, 10, and 12 mol %. For these concentrations, and all below 40 mol %, no phase with long-range order has been observed in either X-ray or neutron diffraction experiments. The prediction of local defect structure and the interaction between defects is therefore of great interest. This has not been possible to date as the number of possible defect topologies is very large and to perform reliable total energy calculations for all of them would be prohibitively expensive. Previous theoretical studies have only considered a selection of representative structures. In this study, a comprehensive search for low-energy defect structures using a combined classical modeling and density functional theory approach is used to identify the low-energy isolated defect structures at the dilute limit, 3.2 mol %. Through analysis of energetics computed using the best available Born-Mayer-Huggins empirical potential model, a point charge model, DFT, and a local strain energy estimated in the harmonic approximation, the main chemical and physical descriptors that correlate to the low-energy DFT structures are discussed. It is found that the empirical potential model reproduces a general trend of increasing DFT energetics across a series of locally strain relaxed structures but is unreliable both in predicting some incorrect low-energy structures and in finding some metastable structures to be unstable. A better predictor of low-energy defect structures is found to be the total electrostatic energy of a simple point charge model calculated at the unrelaxed geometries of the defects. In addition, the strain relaxation energ